Pendekatan Saintifik dalam Pembelajaran di SD - Irzal Anderson (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
Scientific approach applied to all subjects of the curriculum implemented in 2013, so that the scientific approach can be interpreted starting point in the learning process by using a scientific method or scientific measures where scientific approaches using scientific measures is to observe the activities, ask, reason, try and form networking. Scientific approach is designed to bring students directly in the scientific process through exercises that can solidify the scientific process into a short period of time. Scientific approach was originally developed for the natural sciences, but the procedures can also be used in all areas, since all the topics can be formulated into something puzzling (problems) that are used as candidate data for research. In the learning process there is not an approach that is most superior to others, these approaches there are disadvantages and advantages of each if used mainly in the learning process, because it is the writing of this article will use the (review) is conducted on the theory of scientific approach to see the advantages as well as deficiencies in the scientific approach. So we can know about the strength or weakness of excellence and scientific approach when used in learning other than science.